ANALISIS VEGETASI HABITAT ANOA (Bubalus sp.) DI KAWASAN HUTAN LINDUNG DESA PADAYORA KECAMATAN PAMONA SELATAN KABUPATEN POSO - Daniel Oktavianus Lapuno; Elhayat Labiro; Abdul Wahid (Universitas Tadulako, 2015)
Anoa (Bubalus sp) is a member of bovidae family and classified to the endemic species of Sulawesi island, Indonesia. This species is categorized as endangered species by IUCN and Appendix II by CITIES. The decreasing of Anoa’s territory has reduced the feed availability in natural habitat. This study was aimed to analyze vegetation of Anoa (Bubalus sp) habitats. Research was performed as field research at protection forest areas, Pandayora village, Pamona Selatan District, Poso Regency, Central Sulawesi. This research was conducted from April through June 2014. Eight sample plots were made by the size of 20x20 m. Ploting was done by purposive sampling method. Hence vegetation date were analysed to determine the density, frequency, dominant, Importance Value Index and the Diversity Index of Shannon-Wienner. The results showed that there were 15 plant species belongs to 13 families at tree level, 15 plant species belongs to 11 families at pole level, 13 plant species belongs to 11 families at sapling level and 8 plant species belongs to 7 families, respectively. Furthermore, the highest Importance Value Index (IVI) at tree level of vegetation wasbejau(Mangifera sp) with value71,18%. At pole level, the highest IVI was Lithocarpus sp.(35,74%). Hence, the highest IVI at sapling level was Erithrina subumbrans (10,14%) while at seedling level was Diplasium sp. (40,27%). In addition, recorded that there were 51 plants species used as food source by anoa. Key words: Vegetation, Habitat, Bubalus sp, Endemic species, Protection Forest